NATURAL GEOGRAPHICAL FEATURES OF MOUNTAINOUS AREAS IN THE SOUTHWESTERN PART OF KASHKADARYA REGION AND SPECIFIC ASPECTS OF THE USE OF MINERALS (International Conference on Multidisciplinary Sciences and Educational Practices, 2025)
This article analyzes the natural geographic features of mountainous regions, with a particular focus on the geological, hydrogeological, stratigraphic, and engineering-geological conditions of the Tubegatan deposit located in the southwestern part of the Qashqadaryo region. The study examines the relief of the area, the composition of geological strata, the distribution of underground waters and their influence on mining operations, as well as karst-related risk factors. The article highlights the technological and ecological challenges associated with the exploitation of mineral resources in mountainous areas and addresses geodynamic conditions encountered during underground mining. The findings contribute valuable scientific and practical insights for the sustainable and safe development of mineral deposits in mountainous terrains.